Amerigo Guasti (Firenze, 31 marzo 1870 (?)-Busto Arsizio, 15 marzo 1926) - Cambiaghi, Gabriella (Drammaturgia, 2022)
Trained at the acting school of Luigi Rasi in Florence, Amerigo Guasti affirmed himself as appreciated Brillante between 19th and 20th century. As well as being a good interpreter, he is a skilled ‘Capocomico’ and director of his own companies. Since 1906 he establishes a permanent collaboration with Dina Galli. He is also a translator and author of dramatic texts, newspaper articles and an autobiographical book.